Human factors engineering for medical devices: European regulation and current issues. (30th September 2020) - Pelayo, Sylvia; Marcilly, Romaric; Bellandi, Tommaso
Abstract: A large proportion of the patient injuries or deaths attributable to medical device (MD) misuse can be eliminated and/or mitigated by adopting an effective human factors and ergonomics (HFE) approach. The implementation of a usability engineering process is now mandatory for MD manufacturers seeking to obtain the European Union's CE Mark. Here, we describe the European Union's HFE regulation and highlight the challenges faced by (i) manufacturers implementing this regulation and (ii) regulatory bodies charged with assessing the compliance of usability files. In Europe, 95% of MD manufacturers are small- and medium-sized enterprises; compliance with the CE Mark regulations is a real challenge to their competitiveness. Levels of knowledge about HFE vary greatly from one regulatory organization to another, which can sometimes lead to very different expectations. We also present the specific use-related risk management approach required by the HFE regulation. Lastly, we focus on the limitations of the HFE regulation for MDs and on future HFE challenges in further reducing and/or eliminating MD use errors. The main challenge is the need to go beyond technology design and the premarket assessment and to look at the postproduction stage; the coupling between an MD and a sociotechnical system can lead to consequences that were not predicted during the design process. This implies the need to consider the emerging properties of technologies in use by involving all the stakeholders.